The Drosophila engrailed protein is phosphorylated by a serine-specific protein kinase. - Gay, N J (1988)
The engrailed gene is required during embryogenesis of Drosophila melanogaster for normal segmental development and for differentiation of posterior compartments. The protein encoded by the engrailed gene contains a homeodomain, has sequence specific DNA binding activity, and has been proposed as a transcriptional regulator. We show here that the engrailed protein, isolated from both cultured cells and embryos, has been modified by a serine-specific protein kinase. This is the first report that homeobox proteins are post-translationally modified. Phosphorylation of the engrailed protein may directly or allosterically modify its function, and offers the possibility that the engrailed protein becomes phosphorylated in response to extracellular, mitogenic or positional stimuli.